Synthesis and reactivity of magnetically diverse Au@ Ni core-shell nanostructures - Bharathan, Vysakh A.; Raj, Govind K.; Joy, Pattayil Alias; Vinod, Chathakudath P. (Particle & Particle Systems Characterization, 2014)
Core-shell bimetallic Au@Ni nanoparticles, with gold cores and thin nickel shells with overall size less than 10 nm, are synthesized and stabilized in pure cubic (fcc) and hexagonal (hcp) phase. Due to their unique crystal, electronic, and geometric structure, they show interesting magnetic and chemical properties. The Au@Ni-fcc is magnetic, whereas Au@Ni-hcp is non-magnetic. Both the bimetallic nanostructures are stable to surface oxidation until 150 degrees C and show excellent catalytic activity for p-nitrophenol reduction reaction.
Keywords: Au-Ni nanoparticles; bimetallic nanostructures; magnetic core-shell nanoparticles; oxidation resistance